Teaching Physics Modeling Using Computer Interfaced Video: The Case of Paper Baskets - Mamolo, C.; Capistrano, N.; van den Berg, E. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 15 No 1 (2003), 2007)
Excerpt In typical high school and BS Physics courses, students study the results of physics rather than the process of doing physics. Even most laboratory work are verification of known results of physics, rather than doing physics with yet unknown results. Students are rarely exposed to a core activity of physicists: modeling. The availability of computer-video interfacing and analysis software, such as Videopoint and Coach, has greatly expanded the possibilities of doing real modeling in physics education at the high school and college levels. In this paper, we present and work out a simple modeling problem on the free fall of paper baskets. Our purpose is to illustrate the possibilities of modeling in the classroom.